The Effect of Promotion Effectiveness on Product Consumer Purchase Intention Erto's Beauty Care Skincare Through Tiktok Social Media - Farida, Farida; Anggraeni, Antika (prodima@fe.uika-bogor.ac.id, 2024)
The Government's decision to implement Large-Scale Social Restrictions (PSBB) in April 2020 had a broad impact on the production process, distribution, and other operational activities, thereby changing consumer consumption patterns for online transactions. Erto's Beauty Care utilizes the social media application TikTok in promotional activities to support its business. The purpose of this study was to determine the effect of promotion effectiveness on consumer purchase intentions for Erto's Beauty Care products using the TikTok application. The type of research used is descriptive quantitative. Based on the results of simple linear regression analysis, the results of the regression coefficient are positive numbers, which means the direction of the X and Y variables is positive, i.e. if the effectiveness of promotion in the TikTok application is higher, the consumer's purchase intention is also higher for Erto's Beauty Care products. From the results of the partial test or t test, it can be concluded that the effectiveness of the promotion has an effect on consumers' purchase intentions for Erto's Beauty Care products.